Seroepidemiological survey of bovine brucellosis in selected Fulani Herds in Kwara State, Nigeria - Aiyedun, Julius Olaniyi; Oludairo, Oladapo Oyedeji; Olorunshola, Isaac Dayo; Furo, Nathan Ahmadu; Olowoleni, Francis Rotimi; Adam, Mohammed; Shoyinka, Shodeinde Vincent Olu (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: Brucellosis is a bacterial zoonotic disease caused by members of the genus Brucella. It causes economic loss and ill health among animals and humans. This study was conducted to determine the prevalence of brucellosis in cattle particularly in White Fulani breed of cattle in Kwara State, Nigeria. Materials and methods: A total of 120 blood samples were collected randomly from the cattle in Kwara State of Nigeria. Sera were separated from the blood samples. The serum was used for the identification of antibodies against Brucella present in it. Three screening tests namely Bovine Brucella Antibody Test (BBAT; ImmunoCombR), Rose Bengal Plate Test (RBPT) and Serum Agglutination Test (SAT) were used for the identification purpose. Results: Based on BBAT, 13.3% (n=16/120) cattle were positive for brucellosis. Similary, 14.2% (n=17/120) and 3.3% (n=4/120 cattle were found to be positive for RBPT and SAT, respectively. The affected cattle were mainly of White Fulani breed with few cross-bred. Conclusion: Results of this study indicates that brucella antibody is circulating in cattle examined in the study area. This calls for urgent public health intervention and routine screening of other domestic animals as well. http://doi.org/10.5455/javar.2017.d212 XML PubReader